FOREIGN EXPERIENCE OF TAXATION OF CITIZENS INCOME AND POSSIBILITIES OF ITS APPLICATION IN RUSSIA - Aleksandrova, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The goal of research is to develop recommendations for improving the mechanism of income taxation in Russia, taking into account the best foreign practices.The framework of studies was the monographic method and the method of comparative analysis of statistics and legislative documents of the financial authorities of Russia and leading foreign countries, as well as methods of modeling and generalization of the results.The necessity of strengthening the social function of income taxation is substantiated. A comparative analysis of modern taxation of personal income in Russia and abroad is carried out. As a result of the research, it was revealed that the main share of this tax is provided by taxing the incomes of the poorest segments of the population, which contradicts the principles of fair taxation.To improve the mechanism of taxation of incomes of Russian citizens, the experience of leading foreign countries in the application of a progressive scale, family taxation, the establishment of a tax-free minimum (allowance) and tax deductions was used. Particular attention is paid to introducing a tax-free minimum into the mechanism for applying standard deductions taking into account the cost of living.